AGE-RELATED MORPHOMETRIC CHARACTERISTICS OF REMODELING OF ARTERIAL BED OF HIND LIMBS IN WHITE RATS WITH EXPERIMENTAL HYPERCHOLESTEROLEMIA - Yuryk, I. I.; Bodnar, Ya. Ya.; Voloshyn, V. D.; Yuryk, Ya. I. (International Journal of Medicine and Medical Research, 2017)
Background. The human organism is constantly affected by metabolic risk factors. All of them for a long time are asymptomatic and often form in early childhood long before clinical manifestations. However, morphogenesis and morphofunctional features of age-related structural changes in blood vessels of different sites are poorly studied. Objective. To evaluate the morphometric characteristics of arterial bed remodeling of hind limbs in white rats of PRA and RA with experimentally induced hypercholesterolemia. Methods. The tissues biopsies from femoral, knee and shin areas were studied by means of histological and morphometric methods. Results. Experimental hypercholesterolemia caused remodeling of vessels with increasing thickness of medial and endothelial layer of vessels in the investigated parts of the rats’ body. In this case, the external diameter of vessels increased only in femoral area in the reproductive group of rats. In the group of pre-productive animals, the external diameter of the vessels studied was more or less unaffected. Thus, increased thickness of intima and media led to a decrease in arteries capacity. The depth of vascular lesions and the decrease in functional capacity of blood vessels were directly proportional to the duration of the experiment. In the group of reproductive rats, the changes in vascular bed were more evident. Conclusions. Objective study of the processes allows providing a scientific basis for further research and understanding of the pathomorphism of vascular diseases in humans.